The Relationship of Kinship and Rebu in Karonese Culture - hanna meyti Br sitepu; indriani triandjojo (Jurnal CULTURE (Culture, Language, and Literature Review), 2015)
Knowledge and behavior which are socially transmitted are called culture. Culture is shared by some group of people. Culture is abstract. It is located in the idea of human who lives in community. In more traditional definitions of the term, culture is said to embody the best that has been thought and said in society. People who live in society of course have tradition in their community. It can be seen from their way of life, how they interact to their relatives, and how they address their relatives. In this research, the writer discusses about the relationship of kinship in a community which influences the way of communication with certain relatives. The cultural community which becomes the object of this research is Karo culture. Karo has a tradition which is known as rebu. Rebu is a prohibition of direct communication with certain relatives.  The used data are primary data and secondary data. The methods of data collection are metode simak, metode cakap and metode introspeksi. In analyzing the data, the writer uses sociolinguistics as metode padan. While method of data presentation which is used by the writer is descriptive study with informal method.  From the results of the research, it can be concluded that rebu tradition in Karo culture, relation between mami-kela, bengkila-permain and erturangku, are not allowed  to communicate directly. In establishing a communication, they have to use the third person as intermediary.  Keywords : Sociolinguistics, Karo culture, rebu, kinship.